2011
DOI: 10.5056/jnm.2011.17.3.287
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Histamine-2 Receptor Antagonists and Proton Pump Inhibitors on the Rate of Gastric Emptying: A Crossover Study Using a Continuous Real-Time C Breath Test (BreathID System)

Abstract: Background/AimsThe effects of Histamine-2 receptor antagonists and proton pump inhibitors on the gastrointestinal motility have not yet been sufficiently investigated. The aim of this study was to determine the effects of intravenous bolus administration of famotidine and omeprazole on the rate of gastric emptying using the continuous 13C breath test (BreathID system, Exalenz Bioscience Ltd, Israel).MethodsTwelve healthy male volunteers participated in this randomized, 3-way crossover study. After fasting over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…It also decreases the examination time and alleviates patient discomfort. Continuous analysis also provides quick, immediate results (20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also decreases the examination time and alleviates patient discomfort. Continuous analysis also provides quick, immediate results (20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…The two test were separated by a washout period of at least 7 days. In both of the experiments, the tests were started after the patients had fasted overnight (at least 8 hours), and the breath test was performed while the subjects were seated for 4 hours (20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: C-acetic Acid Breath Testmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27] PPI induced the delay of gastric emptying in solid food, but there was few literature about prevention of the treatment delayed gastric emptying, and evaluations on dyspeptic symptoms. 8,[28][29][30] Tegaserod (5-HT4 receptor agonist) was used to normalize the delayed gastric empting caused by PPIs in previous study, but tegaserod is out of market from its cardiovascular risk, so there is no proven safe drug which was studied for preventing the PPI induce delayed gastric emptying. In present study, the efficacy of mosapride citrate for preventing the PPI induced gastric emptying was assessed.…”
Section: Discussionmentioning
confidence: 99%
“…"2 As they pointed out, many studies have been conducted to exam the effects of gastric acid suppressants on gastric emptying, however, results from those studies have been controversial. Our study using liquid meals revealed that intravenous administration of gastric acid suppressants had no significant influence on the rate of gastric emptying.…”
mentioning
confidence: 99%